Estimation of settling velocity using generalized reduced gradient (GRG) and hybrid generalized reduced gradient–genetic algorithm (hybrid GRG-GA) - Shivashankar, M.; Pandey, Manish; Zakwan, Mohammad (Acta geophysica, 2022)
This study describes the settling velocity phenomenon and deals with the methods for its estimation. The accuracy of three previously proposed settling velocity equations is also checked in this study. After graphical and statistical analysis, the authors proposed generalized reduced gradient (GRG) and hybrid generalized reduced gradient–genetic algorithm (hybrid GRG-GA) approaches for the estimation of settling velocity. Hybrid GRG-GA-based settling velocity approach showed more precise results than GRG approach. In addition, hybrid GRG-GA and GRG approaches were compared with previously proposed equations using 226 data points. The graphical and statistical analysis shows that the hybrid GRG-GA and GRG approaches give better agreement with observed data points as compared to previously proposed equations. Application of hybrid GRG-GA reduces the sum of square of error in fall velocity by over 70% and 30% on an average as compared to previous equations during training and testing, respectively. This study highlights that the hybrid GRG-GA approach could be efficiently used for calculating the settling velocity.